2013
DOI: 10.1590/s0001-37652013005000032
|View full text |Cite
|
Sign up to set email alerts
|

Developmental anatomy of Cyperus laxus (non-Nranz) and Fimbristylis dichotoma (Kranz) (Cyperaceae, Poales) and tissue continuity

Abstract: The Cyperaceae species are present in different ecosystems and constitute the herbaceous extract. Of the approximately 5,500 species of the family; a third has Kranz anatomy, representing an important characteristic of the taxonomy and phylogeny of the group. In Cyperus laxus L. (non-Kranz) and Fimbristylis dichotoma Vahl (Kranz), development begins with germination that is marked by the emergence of the coleoptiles, followed by the primary root, which is ephemeral. The rhizome originates from the mesocotyl an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The immersion of seeds in water at environmental or warmed temperature breaks seed dormancy due to the removal of soluble inhibitors found in the seed or fruit coat (BRASIL, 2009;LACERDA et al, 2010). In Nature, this is verified to occur due to the action of rains or in flooded areas (MARCOS FILHO, 2005), such as is the case of tall fringe-rush, a species which is found in irrigated rice areas or cultivated plains and drainage channels (BARROS, 2009;SCATENA, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The immersion of seeds in water at environmental or warmed temperature breaks seed dormancy due to the removal of soluble inhibitors found in the seed or fruit coat (BRASIL, 2009;LACERDA et al, 2010). In Nature, this is verified to occur due to the action of rains or in flooded areas (MARCOS FILHO, 2005), such as is the case of tall fringe-rush, a species which is found in irrigated rice areas or cultivated plains and drainage channels (BARROS, 2009;SCATENA, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…It is found infesting lawns, pastures, irrigated rice fields, cultivated plains, drainage channels, alongside roads, and in coastal plains where it flowers almost the whole year. It propagates by means of rhizomes and seeds (BARROS, 2009;ALBUQUERQUE et al, 2012;SCATENA, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amini Rad & Sonboli (2008) studied 10 Iranian species of Cyperus using light microscopy. Anatomical features of some species of Cyperaceae from northeastern Brazil have also been carried out (Martins, Alves, 2009;Martins, Scatena, 2013). The aim of the present study was to examine anatomical evidence in the species of Cyperus distributed in northern Iran, in order to provide additional information for the taxonomic delimitation at genus level.…”
Section: Introductionmentioning
confidence: 99%
“…Cyperus laxus L. is a member of the Cyperaceae family, which is considered to be a weed cosmopolitan weed located in tropical and subtropical regions [ 10 , 11 ]. It was also recently reported that this and other Cyperaceae species have been identified as pioneer plants in tropical aged and long-term oil spill-impacted sites [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%